The theory of imperfect competition: a radical reconstruction - Dewey, Donald (New York: Columbia University Press, 1969)
The book covers the following topics: The Case for Change; The Tangency Solutions; A Geometry of Multiplant Operations; Stable Equilibrium in Imperfect Competition; 'Monopolistic' Competition as a Mathematical Complication; The Case of Impeded Entry; Economic Warfare; Profit, Uncertainty, and Information; and Economic Activity as Learning.
Bibliographical footnotes.
rpm 25/10/2017
Loans
Keywords: Value; Competition, Imperfect; Prices